Using Anime Noises Game in Teaching Animal's Name to Kindergarten Students - Manissha Juliati Jhoni; An Fauziah Rozani Syafei (Universitas Negeri Padang, 2018)
This paper’s aim is to explain how to use Anime Noises Game in teaching Animal’s name for kindergarten students (young learner). Teaching vocabulary to young learner is different from high school students, because young students have different characteristics and learning style. Anime Noises Game is one of the way of teaching that can be used by the teacher to overcome the problems. Anime Noises Game helps students to learn Animal’s name comprehension that have been learned before. The steps in using Anime Noises Game are brainstorming, discussing about the material, and playing the Anime Noises Game. In brainstorming, teacher shows several pictures related to the material along with general questions about the pictures after that. The next step is discussing about the material, teacher teach students name of animal and sound of animal. The next step Anime Noises Game, teacher will guide the students in playing this game that will help them in learning Animal’s Name that has been taught. And the last steps is concluding. In this step, the teacher make the conclusion about the material.